CSUCI Wavelength 2008_10_03 (California State University Channel Islands)
CSUCI Rideshare Week Oct. 6 to 10 The CSUCI campus will celebrate California Rideshare Week, a statewide campaign, to encourage commuters to try an alternative form of transportation to and from campus. Rideshare Week begins Monday, Oct. 6 and ends Friday, Oct. 11. Police and Parking Services encourages everyone on campus to make a pledge to try an alternative method of transportation for his or her commute to CSUCI at least one day during Rideshare Week.